A review of literature: An examination of the correlation between attachment styles and adolescent girls' sexual behaviors. Issue 6 (18th August 2018) - Sentino, Patrice; Thompson, Phyllis L.; Patterson, David; Freeman, Derrick
ABSTRACT: This literature review examines eight studies of parental attachment styles, sexual behavior, and health outcomes among adolescent girls. The review focuses on studies that analyzed the perceived relationships between parents and their adolescent daughters and whether instabilities of life experiences correlated with risky sexual behaviors and if high-risk sexual behaviors were associated with an increase of sexually transmitted infections, unplanned pregnancies, and other poor health outcomes in adolescent girls. Findings show adolescent girls with insecure parental attachment styles were at a higher risk of sexual behaviors, early pregnancies, and transmission of sexually transmitted infections (STI's). The most common finding in the studies reviewed was the significant association of how higher parental communication and monitoring may prevent risky sexual behaviors at an earlier age. Recommendations for mental and health care providers include the development of treatment programs to address the importance of parent-attachment relationships and multifaceted health needs of adolescents girls. Programs can be strengthened by involving other family members, improving parent-daughter communication and relationships and emphasizing system-level change (policy, procedure, practice). Adding these elements may ultimately lead to sustained improvements over time. Future research on other family social factors (e.g., divorce and separation of attachment figure, poverty, and single-parent homes) associated with attachment and high-risk behaviors is warranted. More research is needed to exam how secure attachments among adolescent girls may prevent earlier sexual encounters, unplanned pregnancies, and STI's.